Perancangan Interior Re-Desain Ruang Karaoke dan Lounge Bar Botol Musik di Makassar - Fenny Kurnia Dewi, E. Sheilla Chandra Kurniawan Hedy C. Indrani (Intra, 2013)
Human needs an entertainment space that can accommodate the activities of socializing with others to cause feelings of pleasure.  Various kind of entertainment space can be mall, amusement park, movie theater, and one of them is a karaoke room and lounge bar.  Botol Musik in Makassar is a entertainment space as karaoke room and lounge bar that has been established since 15 years.  Botol Musik requires a new design concept for keep the visitors satisfaction so as not to get bored with the old interior design and it is expected that Botol Musik has its own brand as a corporate identity that will make its special than the other entertainment space in Makassar.  The design of the new interior design is using a unique concept with two different circumstances on the Customize a karaoke room and a lounge bar in the same building one.  Design method is using qualitative methods applied through the process of data exploration until the final design.